The effects of “soft fitness” classes on the psychophysical state of the first-year students - Maskaeva, Tatiana Yu. (Физическое воспитание и студенческий спорт, 2023)
The purpose of this study was to examine the effects of “soft fitness” on the psychophysical state of the firstyear female students. It was assumed that the integrated use of the elements of yoga, Pilates, autogenic training in physical education classes at a university would help reduce the stress levels among the female students, increase emotional stability, develop the control skills in regulating their own psycho-emotional states and, as a result, improve mental and physical well-being. The study was conducted on the basis of the Russian University of Transport with the first-year students aged 17–19 years old, from whom 2 groups were formed, i.e. experimental (EG) (n = 23) and control (CG) (n = 21). In the EG, the classes were conducted using soft fitness means. In the CG, according to the traditional program, general physical training means were used. Research methods included: psychodiagnostic tests such as “Situational and Personal Anxiety Scale” by Spielberger – Khanin, “Assessment of mental activation, interest, emotional tone, tension and comfort” by L. A. Kurgansky – T. A. Nemchina; physical fitness tests (strength endurance, flexibility, vestibular stability); functional tests such as Shtang, Genchi, Serkin, Ruffier index. During the experiment, a significant advantage of the author’s method was established compared to the traditional approach, which was reflected in a significant improvement in indicators of flexibility, static and strength endurance of the core muscles, vestibular stability (balance function), in results of the functional tests (Stange, Genchi, Serkin, Ruffier index) and some indicators of the mental state of the female students from the EG compared to the CG.